Effect of cysteine mutation at ca2+ coordinating residues to the autolysis, folding and hydrophobicity of full length and mature rand protease: molecular dynamics simulation and essential dynamics - Mohd Azrin, Nur Aliyah; Mohamad Ali, Mohd Shukuri; Raja Abd Rahman, Raja Noor Zaliha; Mohd Shariff, Fairolniza; Ahmad Kamarudin, Nor Hafizah; Muhd Noor, Noor Dina (Taylor and Francis Group, 2023)
Rand protease is a serine protease that shared common characteristics with members of the MEROPS S8 subtilisin family. It is thermostable, highly stable in organic solvent and broad in specificity. Many structures of homologous protein solved by X-ray crystallography and NMR have been deposited to Protein Data Bank (PDB) which allowed this study to rely on structure prediction by deep learning to build three-dimensional (3D) structure of full length and mature Rand protease (flRP and mRP). In silico cysteine mutation to 7 predicted high affinity Ca2+ coordinating residues were introduced, and the mutants were subjected to molecular dynamics simulation to study its effect on flRP and mRP. MD simulation showed a marked increase in flexibility of the pro-peptide segment indicating the impact of single cysteine substitution at high affinity Ca2+ coordinating residues to autolysis of flRP. MD simulation for mRP reaffirmed the role of Ca2+ coordinating sites in providing stability to Rand protease. In addition, these residues also affect the autolysis, folding and hydrophobicity of RP. Essential dynamics observed large contribution of the first few eigenvectors of flRP, mRP and their high affinity Ca2+ coordinating residues mutants to the TMSF values which indicates that these values account for a large portion of the overall atomic fluctuations. These results have given a more comprehensive understanding on the role of cysteine substituted Ca2+ coordinating surface loop to the structure of flRP and mRP which are important in contributing to the structural stability of subtilisin.